Selecting an optimal contractual payment model for Istanbul's public bus operators using non-linear mathematical programming. (September 2019) - Canıtez, Fatih; Çelebi, Dilay; Deveci, Muhammet; Kuvvetli, Yusuf
Abstract: In this study, an optimum payment model is suggested for Istanbul's public bus transport operators by modelling the expectations of passengers, operators and the transport authority. Their expectations also involve non-linear relationships, hence a non-linear mathematical programming is utilized in the paper. The commercial payment, gross-cost and performance-based gross cost payment models are the alternatives to be considered instead of the net-cost model due to its service quality problems in Istanbul's context. According to the model results, a gross cost payment model is recommended for Istanbul. By offering a consensus-based middle ground between the transport actors, the model provides a way for improvement in public transport service provision especially for developing cities where regulatory and institutional context is hard to change.